Synthesis and characterization of isocyanate-free polyureas. Issue 1 (6th December 2017) - Dennis, Joseph M.; Steinberg, Limor I.; Pekkanen, Allison M.; Maiz, Jon; Hegde, Maruti; Müller, Alejandro J.; Long, Timothy E.
Abstract : Due to continued health and safety concerns surrounding isocyanates, alternative synthetic routes to obtain urea-containing polymers is gaining much attention. Abstract : Due to continued health and safety concerns surrounding isocyanates, alternative synthetic routes to obtain urea-containing polymers is gaining much attention. Melt polycondensation of urea with diamines achieved polyureas in the absence of catalyst or solvents. 1 H NMR spectroscopy and thermogravimetric analysis confirmed targeted compositions and thermal stability, respectively. Differential scanning calorimetry and dynamic mechanical analysis provided insight into the copolymers' thermal and morphological behavior. A steady increase in the melting temperature across the range of compositions suggested co-crystallization of the different repeating units, in sharp contrast to non-hydrogen bonded copolymers. Furthermore, tunable melt temperatures and mechanical performance illustrated the versatility of these copolymers in high performance applications. Finally, initial biodegradation studies using a naturally occurring, soil enzyme (urease) demonstrated steady degradation over 4 weeks, releasing ammonia as a potential nitrogen source for agricultural applications.